Nivel de resiliencia e insuficiencia renal crónica en paciente en hemodiálisis - Cerezo Coronel, Katherine Lisseth (2019)
The research work arises from the idea of investigating the resilience of a patient suffering from renal failure with hemodialysis treatment, due to the multiple emotional changes that are triggered by the disease and this has a significant impact on the way of acting and thinking about the individual, in order to provide relevant psychological help to improve their quality of life. The low level of resilience of the patient due to the disease is taken into consideration to adapt a therapeutic scheme based on the results of the techniques used for the intervention and discovery of the signs and symptoms presented by the individual; proceeding to perform the psychological intervention to reduce the patient's symptoms, had a satisfactory result in the process for the well-being of him and his family